Electrolyte, battery and electric device
Patent Information
- Application Number
- CN202410232422.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-02-29
AI Technical Summary
但是,铁酸锂在脱锂过程中会同时发生铁和氧的氧化反应,使得容易产生氧气,导致电解液在正极极片处氧化,既消耗了电解液,又使得电解液体系变得不稳定,降低了电池的循环寿命和安全性能
[0016]In this application, when the electrolyte is applied to a battery and the positive electrode includes lithium replenishing particles, the active ions on the positive electrode are continuously consumed during the initial charge-discharge and continuous cycling processes. The lithium replenishing particles can replenish the active ions lost during the charge-discharge cycles, resulting in a higher energy density for the battery. Simultaneously, the lithium replenishing particles release oxygen anions and iron ions while releasing active ions, generating oxygen, which can easily lead to side reactions between the electrolyte and oxygen. In this application, the first additive includes isocyanate. The isocyanate group has high electronegativity of both nitrogen and oxygen, giving it a strong electron-withdrawing ability. Furthermore, as the end group of the chain compound, the isocyanate attracts electrons from adjacent first additives, concentrating the electron cloud at both ends of the chain compound, resulting in high reactivity of the first additive. Furthermore, when the potential in the electrolyte is high, the C=O double bond in the isocyanate group will break, causing adjacent chain compounds to polymerize in pairs to form a film that adheres to the surface of the positive electrode. In other words, the film formed by the first additive adheres to the surface of the lithium replenishment particles, which helps prevent the lithium replenishment particles from releasing oxygen and reduces side reactions between oxygen and the electrolyte, thus improving the stability of the electrolyte. When the electrolyte is used in a battery, it helps improve the cycle performance and safety performance of the battery. In this application, the first additive is a chain compound. Compared with the scheme where the first additive is a cyclic compound, this avoids the ring-opening decomposition of cyclic compounds, which prevents them from polymerizing into a film. This ensures that the first additive undergoes a polymerization reaction to form a film and prevents the electrolyte from reacting with oxygen. In this application, when the mass fraction of the first additive meets the range of 0.01% ≤ w1 ≤ 3%, the mass fraction of the first additive is within a reasonable range. When the electrolyte is applied to a battery, in the first additive, multiple chain compounds with isocyanate end groups intersect in pairs to form a film attached to the surface of the lithium-replenishing particles. The thickness of the film formed by the first additive is within a reasonable range, allowing it to effectively prevent side reactions between the electrolyte and oxygen, and avoiding an excessively thick film that would increase impedance. This results in good stability of the electrolyte, and the electrolyte applied to the battery exhibits both high cycle performance and energy efficiency. However, when the mass fraction of the first additive is too high, the film formed by the first additive becomes too thick. When the electrolyte is applied to the battery, the impedance of active ions detaching from the surface of the positive electrode is high, thus affecting the kinetics of the interface between the positive electrode and the electrolyte, and reducing the energy efficiency of the electrolyte when applied to the battery.When the mass fraction of the first additive is too small, the polymer formed by the first additive is less and difficult to form a film, or the film formed is thinner. The film formed by the first additive is difficult to cover the surface of the lithium replenishment particles, and it is difficult to prevent the electrolyte from reacting with the oxygen released by the lithium replenishment particles. This causes the electrolyte to undergo side reactions and reduce the stability of the electrolyte, thereby reducing the cycle performance and safety performance of the battery when the electrolyte is used in the battery.
Smart Images

Figure CN117878407B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to an electrolyte, a battery, and an electrical device. Background Technology
[0002] With the rapid development of new energy technologies, the requirements for the cycle life of energy storage batteries are becoming increasingly stringent. Adding a small amount of lithium iron ferrite, a lithium replenisher, to the cathode material can effectively compensate for the loss of active lithium during cycling, thereby improving cycle performance. However, during the delithiation process, lithium iron ferrite undergoes an oxidation reaction involving both iron and oxygen, easily generating oxygen. This leads to oxidation of the electrolyte at the cathode, consuming electrolyte and destabilizing the electrolyte system, ultimately reducing the battery's cycle life and safety performance. Summary of the Invention
[0003] In view of this, this application provides an electrolyte, a battery, and an electrical device, wherein the electrolyte has good stability.
[0004] This application provides an electrolyte comprising a first additive, the first additive comprising a chain compound with an isocyanate end group, wherein the mass fraction w1 of the first additive in the electrolyte is in the range of 0.01% ≤ w1 ≤ 3%.
[0005] Furthermore, the chemical formula of the first additive is: OCN-(CH2) n -NCO, where n has a range of 1 ≤ n ≤ 15.
[0006] Furthermore, the electrolyte also includes a second additive and a solvent, wherein the oxidation potential of the second additive is lower than that of the solvent, and the second additive is a borate additive.
[0007] Furthermore, in the electrolyte, the mass fraction w2 of the second additive is in the range of 0.01% ≤ w2 ≤ 3%.
[0008] Further, the second additive includes at least one of lithium difluorooxalate borate, lithium bis(oxalate borate), lithium tetrafluoroborate, lithium tetraborate, lithium tetracyanoborate, lithium difluoroborate, lithium tetra(trifluoromethyl)borate, lithium bis(trifluoromethyl)difluoroborate, lithium dicyanooxalate borate, lithium pentafluoroethyl trifluoroborate, and lithium perfluorotert-butoxy trifluoroborate.
[0009] The present application further provides a battery, comprising: a negative electrode plate, a separator, a positive electrode plate and the electrolyte provided in the present application, wherein the separator is disposed on one side of the negative electrode plate; the positive electrode plate is disposed on a side of the separator facing away from the negative electrode plate, the positive electrode plate comprises a positive active layer and a positive current collector layer, the positive active layer is disposed on a surface of the positive current collector layer, and the positive active layer comprises a plurality of lithium supplementing particles; the electrolyte impregnates at least part of the positive electrode plate and part of the negative electrode plate, and the electrolyte further comprises a lithium salt.
[0010] Further, in the positive active layer, the mass fraction of the lithium supplementing particles is w3; the lithium supplementing particles comprise a matrix and a coating layer, the coating layer is disposed on an outer periphery of the matrix, and the plane shrinkage rate of the matrix is α; then the relational expression: 0.2 ≤ α×w3 / w1 ≤ 1 is satisfied; wherein the chemical formula of the matrix is Li 1+r M 1-p N p O 4-s B s , and 0.1<r<6.1, 0≤p<0.99, 0≤s<0.1 are satisfied; M and N are each selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, and B is selected from at least one of sulfur, nitrogen, fluorine, chlorine and bromine.
[0011] Further, in a cross-section of the positive electrode plate, an area defined by an inner contour of the coating layer is S1, and after the lithium supplementing particles release lithium ions, an area defined by an outer contour of the matrix is S2, then the plane shrinkage rate α of the matrix satisfies the relational expression: α=(S1-S2) / S1×100%, and the range of the plane shrinkage rate α of the matrix is: 5% ≤ α ≤ 40%.
[0012] Further, in the positive active layer, the range of the mass fraction w3 of the lithium supplementing particles is: 0.5% ≤ w3 ≤ 5%.
[0013] Further, at a magnification of 5000 times, in a rectangular region of 22μm×15μm, in a cross-section of the positive electrode plate, the number of the lithium supplementing particles is plural; the sum of areas defined by inner contours of the plurality of coating layers is S3, and after the lithium supplementing particles release lithium ions, the sum of areas defined by outer contours of the plurality of matrixes is S4, then the shrinkage area S of the plurality of lithium supplementing particles during lithium supplementing satisfies the relational expression: S=S3-S4, and S satisfies the range: 80μm 2 ≤S / w1≤500μm 2 .
[0014] Further, the range of the shrinkage area S of the plurality of lithium supplementing particles during lithium supplementing is: 0.1μm2 ≤S≤6μm 2 .
[0015] This application also provides an electrical device, which includes: a device body and a battery provided in this application, wherein the battery supplies power to the device body.
[0016] In this application, when the electrolyte is applied to a battery and the positive electrode includes lithium replenishing particles, the active ions on the positive electrode are continuously consumed during the initial charge-discharge and continuous cycling processes. The lithium replenishing particles can replenish the active ions lost during the charge-discharge cycles, resulting in a higher energy density for the battery. Simultaneously, the lithium replenishing particles release oxygen anions and iron ions while releasing active ions, generating oxygen, which can easily lead to side reactions between the electrolyte and oxygen. In this application, the first additive includes isocyanate. The isocyanate group has high electronegativity of both nitrogen and oxygen, giving it a strong electron-withdrawing ability. Furthermore, as the end group of the chain compound, the isocyanate attracts electrons from adjacent first additives, concentrating the electron cloud at both ends of the chain compound, resulting in high reactivity of the first additive. Furthermore, when the potential in the electrolyte is high, the C=O double bond in the isocyanate group will break, causing adjacent chain compounds to polymerize in pairs to form a film that adheres to the surface of the positive electrode. In other words, the film formed by the first additive adheres to the surface of the lithium replenishment particles, which helps prevent the lithium replenishment particles from releasing oxygen and reduces side reactions between oxygen and the electrolyte, thus improving the stability of the electrolyte. When the electrolyte is used in a battery, it helps improve the cycle performance and safety performance of the battery. In this application, the first additive is a chain compound. Compared with the scheme where the first additive is a cyclic compound, this avoids the ring-opening decomposition of cyclic compounds, which prevents them from polymerizing into a film. This ensures that the first additive undergoes a polymerization reaction to form a film and prevents the electrolyte from reacting with oxygen. In this application, when the mass fraction of the first additive meets the range of 0.01% ≤ w1 ≤ 3%, the mass fraction of the first additive is within a reasonable range. When the electrolyte is applied to a battery, in the first additive, multiple chain compounds with isocyanate end groups intersect in pairs to form a film attached to the surface of the lithium-replenishing particles. The thickness of the film formed by the first additive is within a reasonable range, allowing it to effectively prevent side reactions between the electrolyte and oxygen, and avoiding an excessively thick film that would increase impedance. This results in good stability of the electrolyte, and the electrolyte applied to the battery exhibits both high cycle performance and energy efficiency. However, when the mass fraction of the first additive is too high, the film formed by the first additive becomes too thick. When the electrolyte is applied to the battery, the impedance of active ions detaching from the surface of the positive electrode is high, thus affecting the kinetics of the interface between the positive electrode and the electrolyte, and reducing the energy efficiency of the electrolyte when applied to the battery.When the mass fraction of the first additive is too small, the polymer formed by the first additive is less and difficult to form a film, or the film formed is thinner. The film formed by the first additive is difficult to cover the surface of the lithium replenishment particles, and it is difficult to prevent the electrolyte from reacting with the oxygen released by the lithium replenishment particles. This causes the electrolyte to undergo side reactions and reduce the stability of the electrolyte, thereby reducing the cycle performance and safety performance of the battery when the electrolyte is used in the battery. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementations of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0018] Figure 1 This is a cross-sectional structural diagram of a battery according to an embodiment of this application;
[0019] Figure 2 This is a schematic cross-sectional view of the positive electrode sheet according to an embodiment of this application;
[0020] Figure 3 This is a scanning electron microscope image of lithium-replenishing particles after shrinkage, according to an embodiment of this application.
[0021] Figure 4 This is a scanning electron microscope image of lithium-replenishing particles after shrinkage, according to another embodiment of this application.
[0022] Figure 5 This is a circuit block diagram of an electrical device according to an embodiment of this application;
[0023] Figure 6 This is a schematic diagram of the structure of an electrical device according to an embodiment of this application.
[0024] Explanation of reference numerals in the attached figures:
[0025] 100-Electrolyte, 200-Battery, 210-Negative electrode, 220-Separator, 230-Positive electrode, 231-Positive active layer, 232-Positive current collector layer, 300-Electrical equipment, 310-Equipment body. Detailed Implementation
[0026] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0027] The terms "first," "second," etc., in the specification, claims, and accompanying drawings of this application are used to distinguish different objects, not to describe a specific order. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products, or apparatuses.
[0028] In this document, references to "embodiment" or "implementation" mean that a particular feature, structure, or characteristic described in connection with an embodiment or implementation may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0029] With the rapid development of new energy technologies, the requirements for the cycle life of energy storage batteries are becoming increasingly stringent. Adding a small amount of lithium iron ferrite (LFP) to the cathode material can effectively compensate for the loss of active lithium during cycling, thereby improving cycle performance. However, during the delithiation process, LFP undergoes an oxidation reaction involving both iron and oxygen, easily generating oxygen. This leads to oxidation of the electrolyte at the cathode, consuming electrolyte and destabilizing the electrolyte system, thus reducing the battery's cycle life and safety. Furthermore, to achieve better lithium replenishment, high-voltage formation is typically used due to the high delithiation potential (3.5V to 4.0V) of LFP. This makes the electrolyte more susceptible to oxidative decomposition at high voltages, further reducing electrolyte stability.
[0030] Please see Figure 1 and Figure 2 This application provides an electrolyte 100, which includes a first additive. The first additive includes a chain compound with an isocyanate end group. In the electrolyte 100, the mass fraction w1 of the first additive is in the range of 0.01% ≤ w1 ≤ 3%.
[0031] Specifically, the mass fraction w1 of the first additive can be, but is not limited to, 0.01%, 0.05%, 0.09%, 0.15%, 0.2%, 0.3%, 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, and 3%.
[0032] Understandably, the mass fraction w1 of the first additive is the ratio of the mass of the first additive to the mass of the electrolyte 100.
[0033] Understandably, the electrolyte 100 is applied to the battery 200, which is a lithium-ion battery. The battery 200 further includes a negative electrode 210, a separator 220, and a positive electrode 230. The positive electrode 230 includes a positive active layer 231 and a positive current collector layer 232. The positive active layer 231 is disposed on the surface of the positive current collector layer 232 and includes lithium-filled particles. The electrolyte 100 at least partially wets the positive electrode 230 and a portion of the negative electrode 210. During the charging and discharging process of the battery 200, the electrolyte 100 serves as a transport medium for active ions, i.e., a transport medium for lithium ions. On the one hand, it provides some active lithium ions for use as conductive ions; on the other hand, the electrolyte 100 provides ion channels to help lithium ions move freely within the battery 200. The lithium replenishing particles can release lithium ions when the battery 200 is being charged, so as to replenish the active ions consumed in the electrolyte 100.
[0034] Understandably, the higher the maximum charging voltage of the battery 200, the more lithium ions are released from the lithium replenishing particles, and the higher the potential of the electrolyte 100.
[0035] Understandably, the first additive comprises a plurality of chain compounds with isocyanate end groups. In the terminology of this application, "a plurality of" means two or more.
[0036] In this embodiment, when the electrolyte 100 is applied to the battery 200 and the positive electrode 230 includes lithium replenishing particles, during the initial charge-discharge and continuous cycling processes of the battery 200, the active ions of the positive electrode 230 are continuously consumed. The lithium replenishing particles can replenish the active ions lost by the battery 200 during charge-discharge cycles, resulting in a higher energy density for the battery 200. Simultaneously, the lithium replenishing particles release oxygen anions and iron ions while releasing active ions, generating oxygen, which can easily cause side reactions between the electrolyte 100 and oxygen. In this embodiment, the first additive includes isocyanate. The isocyanate has high electronegativity of both nitrogen and oxygen, giving it a strong electron-withdrawing ability. Furthermore, as the end group of the chain compound, the isocyanate attracts electrons from adjacent first additives and concentrates the electron cloud at both ends of the chain compound, resulting in higher reactivity of the first additive. Furthermore, when the potential in the electrolyte 100 is high, the C=O double bond in the isocyanate group will break, causing adjacent chain compounds to polymerize in pairs to form a film that adheres to the surface of the positive electrode 230. In other words, the film formed by the first additive adheres to the surface of the lithium replenishment particles, which helps to prevent the lithium replenishment particles from releasing oxygen and reduces side reactions between oxygen and the electrolyte 100, thereby improving the stability of the electrolyte 100. When the electrolyte 100 is used in the battery 200, it helps to improve the cycle performance and safety performance of the battery 200. In this embodiment, the first additive is a chain compound. Compared with the scheme where the first additive is a cyclic compound, it can avoid the ring-opening decomposition of cyclic compounds, which prevents them from polymerizing into a film, ensuring that the first additive undergoes a polymerization reaction to form a film and prevents the electrolyte 100 from reacting with oxygen. In this embodiment, when the mass fraction of the first additive meets the range of 0.01% ≤ w1 ≤ 3%, the mass fraction of the first additive is within a reasonable range. When the electrolyte 100 is applied to the battery 200, in the first additive, multiple chain compounds with isocyanate end groups intersect in pairs to form a film attached to the surface of the lithium-replenishing particles. The thickness of the film formed by the first additive is within a reasonable range, enabling the first additive to effectively prevent side reactions between the electrolyte 100 and oxygen, and avoiding excessively thick films that increase impedance. This results in good stability of the electrolyte 100, and the electrolyte 100 applied to the battery 200 exhibits both high cycle performance and energy efficiency. However, when the mass fraction of the first additive is too high, the film formed by the first additive becomes too thick. When the electrolyte 100 is applied to the battery 200, the impedance of active ions detaching from the surface of the positive electrode 230 is high, thus affecting the kinetic performance of the interface between the positive electrode 230 and the electrolyte 100, and reducing the energy efficiency of the electrolyte 100 applied to the battery 200.When the mass fraction of the first additive is too small, the polymer formed by the first additive is less and difficult to form a film, or the film formed is thinner. The film formed by the first additive is difficult to cover the surface of the lithium replenishment particles, and it is difficult to prevent the electrolyte 100 from reacting with the oxygen released by the lithium replenishment particles. This causes the electrolyte 100 to undergo side reactions and reduce the stability of the electrolyte 100, thereby reducing the cycle performance and safety performance of the battery 200 when the electrolyte 100 is used.
[0037] Optionally, the first additive includes an alkyl diisocyanate.
[0038] In some embodiments, the chemical formula of the first additive is: OCN-(CH2) n -NCO, where n has a range of 1 ≤ n ≤ 15.
[0039] Specifically, the value of n can be, but is not limited to, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, and 15.
[0040] In this embodiment, the chemical formula of the first additive is OCN-(CH2). n If the carbon chain length of the chain compound is -NCO and n satisfies the range 1≤n≤15, then the carbon chain length of the chain compound is within a reasonable range. When the mass fraction of the first additive is constant, the mass proportion of the functional group isocyanate in the first additive is also within a reasonable range, which is beneficial for the polymerization reaction of two adjacent chain compounds and their adhesion to the surface of the lithium replenishment particles, further preventing the side reaction between electrolyte 100 and oxygen, thus giving the electrolyte 100 better cycle performance and safety performance when applied to the battery 200. Furthermore, it avoids increasing the impedance of the film formed by the first additive due to excessively long carbon chains of the chain compounds, thereby giving the electrolyte 100 higher energy efficiency when applied to the battery 200. When the value of n is too large, when the mass fraction of the first additive is constant, the carbon chain of the chain compound is too long, resulting in a smaller mass proportion of isocyanate, which is not conducive to the polymerization reaction of two adjacent chain compounds and the formation of a film that adheres to the surface of the lithium replenishment particles, making it difficult to prevent the side reaction between electrolyte 100 and oxygen. Furthermore, when the first additive undergoes a polymerization reaction and forms a film, the interfacial impedance between the electrolyte 100 and the film becomes too large, thereby reducing the energy efficiency of the electrolyte 100 when applied to the battery 200.
[0041] In some embodiments, the electrolyte 100 further includes a second additive and a solvent, wherein the oxidation potential of the second additive is lower than that of the solvent, and the second additive is a borate additive.
[0042] Understandably, borate additives include boron atoms, which can form strong chemical bonds with oxygen atoms, resulting in a low oxidation potential for the borate additives.
[0043] In this embodiment, the oxidation potential of the second additive is lower than that of the solvent. When the electrolyte 100 is applied to the battery 200 and the battery 200 is charged, the potential of the positive electrode 230 continuously rises. At the interface between the positive electrode 230 and the electrolyte 100, the second additive reaches its oxidation potential earlier than the solvent. This allows the second additive to undergo oxidation reaction more preferentially than the solvent, preventing the solvent from oxidizing and decomposing to produce gas that could affect the stability of the electrolyte 100. This improves the oxidation resistance of the electrolyte 100 and extends the service life of the battery 200 when the electrolyte 100 is applied to the battery 200. Furthermore, the second additive in the electrolyte 100 is a borate additive. The boron atoms in the second additive are electron-deficient and readily combine with oxygen anions, thereby preventing iron ions from combining with oxygen anions and reducing the generation of oxygen. This reduces the side reactions between the electrolyte 100 and oxygen, which helps to improve the stability of the electrolyte 100 and, consequently, improves the cycle performance and safety performance of the battery 200 when the electrolyte 100 is used.
[0044] Optionally, if the difference between the oxidation potential of the solvent and the oxidation potential of the second additive is U1, then U1 satisfies the range: 0.8V≤U1≤2V.
[0045] Specifically, the value of U1 can be, but is not limited to, 0.8V, 0.9V, 1V, 1.1V, 1.2V, 1.3V, 1.4V, 1.5V, 1.6V, 1.7V, 1.8V, 1.9V, and 2V.
[0046] In this embodiment, when the difference U1 between the oxidation potential of the solvent and the oxidation potential of the second additive satisfies the range of 0.8V≤U1≤2V, the potential difference between the oxidation potential of the solvent and the oxidation potential of the second additive is within a reasonable range. This ensures that when the battery 200 is charged, even when the oxidation potential of the second additive is reached and the second additive undergoes oxidation, the potential of the battery 200 has not yet reached the oxidation potential of the solvent. This effectively prevents the solvent from undergoing oxidative decomposition and generating gas, which would affect the stability of the electrolyte 100 and is beneficial for effectively improving the oxidation resistance of the electrolyte 100.
[0047] In some embodiments, in the electrolyte 100, the mass fraction w2 of the second additive is in the range of 0.01% ≤ w2 ≤ 3%.
[0048] Specifically, the mass fraction w2 of the second additive can be, but is not limited to, 0.01%, 0.05%, 0.09%, 0.15%, 0.2%, 0.3%, 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, and 3%.
[0049] Understandably, the mass fraction of the second additive is the ratio of the mass of the second additive to the mass of the electrolyte 100.
[0050] In the electrolyte 100 provided in this embodiment, when the mass fraction w2 of the second additive meets the range of 0.01% ≤ w2 ≤ 3%, the mass fraction of the second additive is within a reasonable range. When the electrolyte 100 is applied to the battery 200, on the one hand, the boron atom content in the second additive is within a reasonable range, which can combine with the oxygen negative ions released by the lithium replenishment particles to generate oxygen, thereby mitigating the side reaction between the electrolyte 100 and oxygen, and thus improving the stability of the electrolyte 100 and the cycle performance and safety performance of the battery 200 when applied to the battery 200. In addition, it can also avoid the reduction reaction caused by an excessively high mass fraction of the second additive and the increase in the interfacial impedance between the positive electrode 230 and the electrolyte 100, so that the electrolyte 100 also has high energy efficiency when applied to the battery 200. When the mass fraction of the second additive is too high, the excess additive may adhere to the interface between the positive electrode 230 and the electrolyte 100, undergo a reduction reaction, and generate decomposition products that adhere to the surface of the positive electrode 230. This increases the resistance to the insertion and extraction of active ions on the positive electrode 230, resulting in lower energy efficiency of the battery 200 when the electrolyte 100 is used. When the mass fraction of the second additive is too low, the amount of boron atoms in the second additive is too small when the electrolyte 100 is used in the battery 200. This means that the boron atoms can only combine with a small number of oxygen anions. During the charging process of the battery 200, other oxygen anions released by the lithium replenishment particles can still react with iron ions to generate oxygen, which exacerbates the side reactions between the electrolyte 100 and oxygen, thereby reducing the stability of the electrolyte 100 and thus reducing the cycle performance and safety performance of the battery 200 when the electrolyte 100 is used.
[0051] Optionally, the borate additive includes lithium ions.
[0052] In this embodiment, the borate additive includes lithium ions. When the second additive is a borate additive and is applied to the battery 200, the borate additive can act as a lithium replenisher for the electrolyte 100. The borate additive can release lithium ions, thereby replenishing the lithium ions lost in the electrolyte 100, which is beneficial to improving the cycle performance and energy density of the battery 200 when the electrolyte 100 is applied to the battery 200.
[0053] In some embodiments, the second additive includes at least one of lithium difluorooxalate borate, lithium bis(oxalate borate), lithium tetrafluoroborate, lithium tetraborate, lithium tetracyanoborate, lithium difluoroborate, lithium tetra(trifluoromethyl)borate, lithium bis(trifluoromethyl)difluoroborate, lithium dicyanooxalate borate, lithium pentafluoroethyl trifluoroborate, and lithium perfluorotert-butoxy trifluoroborate.
[0054] Understandably, in this embodiment, "at least one" means one or more.
[0055] In this embodiment, lithium difluorooxalate borate, lithium bis(oxalate borate), lithium tetrafluoroborate, lithium tetraborate, lithium tetracyanoborate, lithium difluoroborate, lithium tetra(trifluoromethyl)borate, lithium bis(trifluoromethyl)difluoroborate, lithium dicyanooxalate borate, lithium pentafluoroethyl trifluoroborate, and lithium perfluorotert-butoxy trifluoroborate all contain boron atoms. When the electrolyte 100 is applied to the battery 200, the boron atoms in the second additive can combine with oxygen anions to reduce the amount of oxygen generated by the reaction of oxygen anions with iron ions, further slowing down the side reaction between the electrolyte 100 and oxygen, and improving the stability of the electrolyte 100. Furthermore, since the second additive also contains boron atoms, it has a lower oxidation potential than the solvent. When the battery 200 is charged, the second additive can preferentially induce oxidation in the solvent, thereby preventing the solvent from decomposing and generating gas that could damage the stability of the electrolyte 100. Furthermore, the cations of lithium difluorooxalate borate, lithium bis(oxalate borate), lithium tetrafluoroborate, lithium tetraborate, lithium tetracyanoborate, lithium difluoroborate, lithium tetra(trifluoromethyl)borate, lithium bis(trifluoromethyl)difluoroborate, lithium dicyanooxalate borate, lithium pentafluoroethyl trifluoroborate, and lithium perfluorotert-butoxytrifluoroborate are all lithium ions. This ensures that when the electrolyte 100 is applied to the battery 200, on the one hand, it avoids the introduction of other cations into the electrolyte 100, which would result in excessive impurities in the electrolyte 100, thereby further improving the stability of the electrolyte 100; on the other hand, the second additive can release lithium ions, thereby replenishing the lithium ions lost in the electrolyte 100, which is beneficial to further improving the cycle performance of the battery 200 when the electrolyte 100 is applied to the battery 200.
[0056] Optionally, the solvent includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, methyl ethyl carbonate, dimethyl carbonate, ethyl acetate, ethyl propionate, propyl propionate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and ethylene glycol dimethyl ether.
[0057] Optionally, in the electrolyte 100, the mass fraction w4 of the solvent ranges from 75% to 84%. Specifically, the value of the mass fraction w4 of the solvent can be, but is not limited to, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%, 78.5%, 79%, 79.5%, 80%, 81%, 81.5%, 82%, 83%, and 84%. When the mass fraction of the solvent is within a reasonable range, it can sufficiently dissolve the first additive and the second additive.
[0058] Optionally, the electrolyte 100 further includes a lithium salt, and the solvent is used to dissolve the lithium salt and the first additive and the second additive. The lithium salt includes active ions, namely lithium ions.
[0059] Optionally, the lithium salt includes at least one selected from lithium hexafluorophosphate, lithium difluorosulfonylimide, lithium difluorophosphate, lithium trifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, and lithium perchlorate. Wherein, at least one of lithium hexafluorophosphate, lithium difluorosulfonylimide, lithium difluorophosphate, lithium trifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, and lithium perchlorate is dissolved in a solvent to provide sufficient active ions, i.e., lithium ions, for the electrolyte 100.
[0060] Optionally, the electrolyte 100 further includes a third additive, which is a film-forming additive.
[0061] In this embodiment, when the electrolyte 100 is applied to the battery 200, the third additive helps to promote the formation of an interface film between the positive electrode 230 and / or the negative electrode 210 and the electrolyte 100, and can maintain the stability of the interface film between the positive electrode 230 and / or the negative electrode 210 and the electrolyte 100, so as to avoid the increase of the internal resistance of the battery 200 due to the destruction of the interface film, thereby enabling the battery 200 to have a high energy efficiency when the electrolyte 100 is applied to the battery 200.
[0062] Optionally, in the electrolyte 100, the ratio of the total mass of the first additive, the second additive, and the third additive to the mass of the electrolyte 100 is w5, and w5 satisfies the range: 1% ≤ w5 ≤ 15%.
[0063] Specifically, the value of w5 can be, but is not limited to, 1%, 1.5%, 1.8%, 2%, 2.2%, 2.8%, 3%, 3.5%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 7%, 8%, 9%, 9.5%, 10%, 10.5%, 11%, 12%, 13%, 14%, and 15%.
[0064] Understandably, w5 is the ratio of the mass of all additives in the electrolyte 100 to the mass of the electrolyte 100; in other words, w5 is the mass fraction of all additives in the electrolyte 100.
[0065] In this embodiment, when the ratio w5 of the total mass of the first additive, the second additive, and the third additive to the mass of the electrolyte 100 satisfies the range of 1% ≤ w5 ≤ 15%, the mass fraction of the additives in the electrolyte 100 is within a reasonable range, so as to avoid side reactions with the solvent caused by excessive additives, which is beneficial to improving the stability of the electrolyte 100.
[0066] This application also provides a battery 200, which includes: a negative electrode 210, a separator 220, a positive electrode 230, and an electrolyte 100 provided in this application. The separator 220 is disposed on one side of the negative electrode 210; the positive electrode 230 is disposed on the side of the separator 220 opposite to the negative electrode 210, and the positive electrode 230 includes a positive active layer 231 and a positive current collector layer 232. The positive active layer 231 is disposed on the surface of the positive current collector layer 232, and the positive active layer 231 includes a plurality of lithium replenishing particles; the electrolyte 100 at least wets a portion of the positive electrode 230 and a portion of the negative electrode 210, and the electrolyte 100 also includes lithium salt.
[0067] Understandably, the positive electrode 230, the diaphragm 220, and the negative electrode 210 are arranged sequentially.
[0068] Understandably, in the battery 200, the electrolyte 100 includes lithium salt and active ions, namely lithium ions; the positive electrode 230 and the negative electrode 210 are at least partially immersed in the electrolyte 100. During the charging and discharging process of the battery 200, the electrolyte 100 serves as a transport medium for active ions, namely lithium ions. On the one hand, it can provide some active lithium ions for use as conductive ions; on the other hand, the electrolyte 100 can provide ion channels to help lithium ions move freely in the battery 200.
[0069] In the battery 200 provided in this embodiment, the positive electrode active layer 231 of the positive electrode 230 includes lithium replenishing particles. During the initial charge-discharge and continuous cycling processes, the active ions of the positive electrode 230 are continuously consumed. The lithium replenishing particles can release lithium ions to replenish the active ions lost by the battery 200 during charge-discharge cycles, thus giving the battery 200 a high energy density and high initial efficiency. Furthermore, the battery 200 includes the electrolyte 100 provided in this application. The electrolyte 100 includes a first additive, which can undergo a polymerization reaction to form a film and adhere to the surface of the positive electrode 230. This prevents the oxygen released from the lithium replenishing particles from reacting with the electrolyte 100, improving the stability of the electrolyte 100. Ultimately, this results in the battery 200 having high energy efficiency, as well as good cycle performance and safety performance.
[0070] Optionally, the battery 200 can be one of cylindrical batteries, prismatic batteries, and pouch batteries.
[0071] Optionally, the material of the diaphragm 220 is selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. In some embodiments, the diaphragm 220 is a single-layer film; in other embodiments, the diaphragm 220 is a multilayer composite film. When the diaphragm 220 is a multilayer composite film, the material of each layer can be the same or different.
[0072] Optionally, the thickness of the diaphragm 220 is in the range of 14μm to 18μm. Specifically, the thickness of the diaphragm 220 can be, but is not limited to, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, 16.5μm, 17μm, 17.5μm and 18μm.
[0073] Optionally, the positive electrode active layer 231 further includes a positive electrode active material, which is selected from at least one of lithium transition metal oxides and their modified materials. In some embodiments, the positive electrode active material is lithium iron phosphate. The modified material may be a lithium transition metal oxide that has undergone doping modification and / or coating modification. Preferably, the lithium transition metal oxide may be, but is not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0074] Optionally, the material of the positive electrode current collector layer 232 is selected from aluminum.
[0075] Optionally, the positive electrode active layer 231 further includes a positive electrode binder and a positive electrode conductive agent. In the positive electrode active layer 231, the positive electrode binder is used to bind the components in the positive electrode active layer 231 to improve the overall performance of the positive electrode sheet 230; the positive electrode conductive agent can improve the conductivity of the positive electrode active layer 231.
[0076] Optionally, the positive electrode binder is selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride, and polytetrafluoroethylene.
[0077] Optionally, the positive electrode conductive agent is selected from at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0078] Optionally, the negative electrode 210 includes a negative electrode current collector layer (not shown) and a negative electrode active layer (not shown). The negative electrode active layer is disposed on the surface of the negative electrode current collector layer. The negative electrode active layer includes a negative electrode active material selected from at least one of lithium metal, artificial graphite, natural graphite and graphene and other composite materials.
[0079] Optionally, the negative electrode current collector layer is selected from copper.
[0080] Optionally, the negative electrode active layer further includes a negative electrode binder, a negative electrode conductive agent, and a negative electrode thickener. The negative electrode binder is used to bind the components in the negative electrode active layer and improve the overall performance of the negative electrode active layer. The negative electrode conductive agent is used to improve the conductivity of the negative electrode active layer. The thickener is used to improve the adhesion of the negative electrode active layer.
[0081] Optionally, the negative electrode conductive agent is selected from at least one of acetylene black, conductive carbon black, carbon nanotubes, carbon fibers, graphene, etc.
[0082] Optionally, the negative electrode binder includes at least one of asphalt binder, styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyacrylate, carboxymethyl cellulose (CMC), sodium alginate, etc.
[0083] Optionally, the negative electrode thickener is selected from at least one of sodium carboxymethyl cellulose (CMC), polyacrylamide (PAM), and polymethyl methacrylate (PMA).
[0084] In some embodiments, in the positive electrode active layer 231, the mass fraction of the lithium supplement particles is w3; the lithium supplement particles comprise a matrix and a coating layer, the coating layer is disposed on the outer periphery of the matrix, and the plane shrinkage rate of the matrix is α; the relational expression 0.2 ≤ α×w3 / w1 ≤ 1 is satisfied; wherein the chemical formula of the matrix is Li 1+r M 1-p N p O 4-s B s , which satisfies 0.1<r<6.1, 0≤p<0.99, 0≤s<0.1; M and N are each selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, and B is selected from at least one of sulfur, nitrogen, fluorine, chlorine and bromine.
[0085] Specifically, the value of α×w3 / w1 can be, but is not limited to, 0.2, 0.25, 0.3, 0.35, 0.4, 0.46, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 and 1, etc.
[0086] Understandably, the chemical formula of the matrix is Li 1+r M 1-p N p O 4-s B s , then the matrix is made of Li 1+r M 1-p N p O 4-s B s formed.
[0087] Specifically, the value of r can be, but is not limited to, 0.2, 0.4, 0.7, 0.9, 1.0, 1.3, 1.5, 1.7, 2.2, 2.5, 2.8, 3.2, 3.5, 3.7, 4.5, 4.8, 4.9, 5.1, 5.3, 5.5, 5.6, 5.8, 5.9 and 6.0, etc.
[0088] Specifically, the value of p can be, but is not limited to, 0, 0.05, 0.09, 0.1, 0.15, 0.18, 0.22, 0.25, 0.28, 0.35, 0.39, 0.45, 0.48, 0.55, 0.59, 0.6, 0.65, 0.68, 0.7, 0.75, 0.79, 0.85, 0.88, 0.9, 0.94 and 0.99, etc.
[0089] Specifically, the value of s can be, but is not limited to, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08 and 0.09, etc.
[0090] Understandably, the product of the planar shrinkage ratio α of the substrate and the mass fraction w3 of the lithium replenishment particles can characterize the total lithium release of the plurality of lithium replenishment particles in the positive electrode active layer 231; the larger the value of α×w3, the larger the total lithium release of the plurality of lithium replenishment particles; the smaller the value of α×w3, the smaller the total lithium release of the plurality of lithium replenishment particles.
[0091] In this embodiment, the lithium replenishing particles include a substrate and a coating layer, with the coating layer disposed on the outer periphery of the substrate. On one hand, the coating layer covers and protects the substrate, preventing it from reacting with air and becoming oxidized, thus ensuring that the lithium replenishing particles can replenish lithium during battery 200 charging, which is beneficial for improving the performance of the lithium replenishing particles. On the other hand, the coating layer has conductive properties. When active ions in the substrate are intercalated or deintercalated, they can pass through the coating layer into the electrolyte 100. The coating layer can reduce the impedance of the active ions extracted from the lithium replenishing particles, which is beneficial for improving the rate performance of the battery 200. In this embodiment, α×w3 / w1 satisfies the range 0.2≤α×w3 / w1≤1. Therefore, during the charging and discharging process of the battery 200, the amount of lithium released by the lithium replenishing particles and the mass content of the first additive are both within a reasonable range. The lithium ions released by the lithium replenishing particles can promptly replenish the lithium ions lost by the battery 200 during charging and discharging, resulting in a higher energy density for the battery 200. Meanwhile, the oxygen released by the lithium replenishing particles is within a reasonable range, avoiding excessive side reactions between the electrolyte 100 and oxygen due to excessive oxygen. The film formed by the polymerization reaction of the first additive can adhere to the surface of the positive electrode 230. In other words, the film formed by the first additive can adhere to the surface of the lithium replenishing particles to prevent the oxygen released by the lithium replenishing particles from reacting with the electrolyte 100, thereby giving the electrolyte 100 higher stability and the battery 200 better cycle performance and safety performance. When the value of α×w3 / w1 is too large, the mass fraction and planar shrinkage rate of the lithium replenishing particles in the battery 200 are too large, or the mass fraction of the first additive is too small. When the battery 200 is charged, the total amount of lithium ions released by the lithium replenishing particles is too large. Although this can replenish the active ions lost by the battery 200 during charging and discharging, it will also generate too much oxygen. If the mass fraction of the first additive is too small, it will be difficult for the first additive to polymerize into a film, or the polymerized film will be too thin. This makes it difficult for the first additive to adhere to the surface of the lithium replenishment particles, causing oxygen generated by the lithium replenishment particles to still leak out and react with the electrolyte 100, resulting in poor stability of the electrolyte 100. Consequently, the cycle performance and safety performance of the battery 200 will be poor. When the value of α×w3 / w1 is too small, the mass fraction and planar shrinkage rate of the lithium replenishment particles in the battery 200 will be too small, or the mass fraction of the first additive will be too large. When the battery 200 is charged, the total amount of lithium ions released by the lithium replenishment particles will be too small, and the lithium replenishment particles will be unable to replenish the active ions lost by the battery 200 during charging and discharging.Furthermore, the first additive has an excessively high mass proportion in the electrolyte 100, and the film formed by the polymerization reaction of the first additive is relatively thick, which increases the resistance of active ions to escape from the surface of the positive electrode 230, thereby affecting the energy density and energy efficiency of the battery 200.
[0092] Optionally, in some embodiments, the matrix is lithium ferrite with the chemical formula Li5FePO4. Optionally, in other embodiments, the matrix has the chemical formula Li6CoO4.
[0093] Optionally, in some embodiments, the coating layer is a carbon coating layer, the coating layer is conductive, and the coating layer can protect the substrate it encapsulates to improve the oxidation resistance of the lithium replenishment particles.
[0094] Alternatively, in other embodiments, the chemical formula of the coating layer is: Z x O y @C, wherein Z is selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, and the type of Z is the same as the type of M in the matrix, and the coating layer also satisfies the relationship: 1≤x≤3, 1≤y≤5.
[0095] Understandably, the chemical formula of the lithium replenishing particles is Li. 1+r M 1-p N p O 4-s B s @Z x O y @C, then the lithium replenishment particles are made of Li 1+r M 1-p N p O 4-s B s Z x O y and C formation, the lithium replenishing particles are in Li 1+r M 1-p N p O 4-s B s For the kernel, and Z x O y Enclosing the outer periphery of the kernel, where Z x O y An oxide layer is formed to prevent the core from being oxidized and corroded by external factors; then, carbon is coated around the oxide layer to form a carbon layer, which is used to improve the conductivity of the coating layer. In other words, the coating layer includes an oxide layer and a carbon layer disposed sequentially, with the oxide layer disposed between the carbon layer and the substrate.
[0096] Specifically, the value of x can be, but is not limited to, 1, 1.2, 1.3, 1.5, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.4, 2.6, 2.7, 2.8, 2.9 and 3.
[0097] Specifically, the value of y can be, but is not limited to, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2.0, 2.2, 2.4, 2.5, 2.7, 2.8, 2.9, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.1, 4.3, 4.5, 4.6, 4.7, 4.9, and 5.
[0098] In this embodiment, the chemical formula of the coating layer is Z. x O y @C, the coating layer consists of an oxide layer and a carbon layer, with the oxide layer positioned closer to the substrate than the carbon layer. The oxide layer protects the substrate from oxidation by air oxygen, ensuring the substrate can release lithium ions to replenish the lithium-ion battery 200. Furthermore, the type of Z is the same as the type of M in the substrate, avoiding the introduction of excessive heteroatoms and improving the uniformity of the replenishing particles. Moreover, the coating layer also includes carbon, which coats the oxide layer to form a carbon layer. This improves the conductivity of the replenishing particles, reduces the resistance of active ions entering the electrolyte 100 from the substrate and coating layer, and thus improves the energy efficiency of the lithium-ion battery 200.
[0099] Understandably, in the cross-section of the positive electrode 230, the area defined by the inner contour of the coating layer is S1, and the area defined by the outer contour of the substrate after the lithium replenishment particle releases lithium ions is S2. Then the planar shrinkage rate α of the substrate satisfies the relationship: α=(S1-S2) / S1×100%.
[0100] Understandably, the cross-section of the positive electrode 230 is obtained by cutting the positive electrode 230 using an ion beam polishing (CP) instrument.
[0101] In this embodiment, during the lithium ion release process of the lithium replenishment particle, the substrate shrinks due to the decrease in lithium content, while the shape of the coating layer remains unchanged. Therefore, in this embodiment, the area S1 defined by the inner contour of the coating layer is the area of the substrate before shrinkage, and the area S2 defined by the outer contour of the substrate after lithium ion release is the area of the substrate after shrinkage. The difference between S1 and S2 represents the area of the substrate that shrank during the shrinkage process. The planar shrinkage rate of the substrate can characterize the amount of lithium released by a single lithium replenishment particle during the lithium replenishment process.
[0102] In some embodiments, the planar shrinkage rate α of the matrix is in the range of 5% ≤ α ≤ 40%.
[0103] Specifically, the value of the planar shrinkage rate α of the matrix can be, but is not limited to, 5%, 8%, 9%, 10%, 12%, 14%, 15%, 18%, 20%, 21%, 23%, 25%, 26%, 27%, 28%, 30%, 32%, 33%, 34%, 35%, 36%, 38%, and 40%.
[0104] In this embodiment, when the planar shrinkage rate α of the substrate satisfies the range of 5% ≤ α ≤ 40%, the value of the planar shrinkage rate α of the substrate is within a reasonable range. During the charging process of the battery 200, the amount of lithium released by a single lithium replenishment particle during the lithium replenishment process is within a reasonable range. This ensures that the lithium replenishment particle can replenish the lithium ions lost by the battery 200 during charging and discharging, while also preventing the lithium replenishment particle from releasing too much oxygen, which could exacerbate the side reactions with the electrolyte 100. Ultimately, this allows the battery 200 to have both high energy density and good cycle performance and safety performance. When the planar shrinkage rate of the substrate is too large, the amount of lithium released by a single lithium replenishment particle during the lithium replenishment process is too large. Similarly, the lithium replenishment particle also releases too much oxygen, which may exacerbate the side reactions between the electrolyte 100 and oxygen, reducing the stability of the electrolyte 100 and the cycle performance of the battery 200. When the planar shrinkage rate of the substrate is too small, the amount of lithium released by a single lithium replenishment particle during the lithium replenishment process is too small. When the positive electrode active layer 231 includes multiple lithium replenishment particles, the amount of lithium ions released by the multiple lithium replenishment particles is too small, making it difficult for the lithium replenishment particles to replenish the lithium ions lost by the battery 200 during the charging and discharging process, thereby reducing the energy density of the battery 200.
[0105] Optionally, when the electrolyte 100 is applied to the battery 200, the amount of lithium ions released by the lithium replenishing particles can be controlled by controlling the maximum formation voltage of the battery 200. The higher the maximum formation voltage of the battery 200, the more lithium ions are released by the lithium replenishing particles; wherein, the maximum formation voltage of the battery 200 is U2, and U2 satisfies the range: 3.85V≤U2≤4.2V.
[0106] Specifically, the maximum charging voltage U2 formed by the battery 200 can be, but is not limited to, 3.85V, 3.86V, 3.88V, 3.89V, 3.9V, 3.92V, 3.93V, 3.94V, 3.96V, 3.98V, 3.99V, 4.0V, 4.02V, 4.05V, 4.08V, 4.1V, 4.12V, 4.13V, 4.15V, 4.16V, 4.18V, 4.19V, and 4.2V.
[0107] In this embodiment, when the charging voltage U2 used to charge the battery 200 satisfies the range of 3.85V≤U2≤4.2V, the maximum charging voltage of the battery 200 is within a reasonable range, making the planar shrinkage rate of the substrate within a reasonable range. Therefore, when the positive electrode 230 is applied to the battery 200 and the battery 200 is charged, the amount of lithium released by the substrate is within a suitable range. The lithium ions released by the substrate can replenish the lithium ions lost by the battery 200 during charging and discharging in a timely manner, thereby improving the initial efficiency, energy density and capacity retention of the battery 200, and also helping to extend the cycle life of the battery 200. When the maximum charging voltage U2 of the battery 200 is too high, the planar shrinkage rate of the substrate is too large. When the positive electrode 230 is applied to the battery 200 and the battery 200 is charged, the amount of lithium released by the substrate is too large. As a result, when the lithium ions move to the negative electrode 210, due to the limitation of the negative electrode dynamics, they cannot all be quickly embedded in the negative electrode. This causes some of the lithium ions to be deposited on the surface of the negative electrode 210, resulting in lithium deposition on the surface of the negative electrode 210. In addition, the substrate releases oxygen at the same time as releasing lithium ions. If the amount of oxygen released in this process is too large, it will cause safety hazards, shorten the cycle life of the battery 200, and reduce the safety performance of the battery 200. When the maximum charging voltage U2 formed by the battery 200 is too small, the planar shrinkage rate of the substrate is too small. Therefore, when the positive electrode 230 is applied to the battery 200 and the battery 200 is charged, the amount of lithium released by the substrate is too small, which reduces the utilization rate of the lithium replenishing particles. Moreover, the lithium ions released by the substrate are difficult to replenish the lost lithium ions, resulting in low initial efficiency, energy density and capacity retention of the battery 200 when the positive electrode 230 is applied to the battery 200. The lithium replenishing particles are unable to play their role in replenishing lithium ions to the battery 200.
[0108] In some embodiments, the mass fraction w3 of the lithium replenishment particles in the positive electrode active layer 231 ranges from 0.5% to w3 to 5%.
[0109] Specifically, the mass fraction w3 of the lithium replenishing particles can be, but is not limited to, 0.5%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.1%, 3.3%, 3.5%, 3.6%, 3.8%, 4%, 4.1%, 4.3%, 4.5%, 4.7%, 4.8%, 4.9%, and 5%.
[0110] In some embodiments, at a magnification of 5000x, within a rectangular region of 22μm × 15μm, in the cross-section of the positive electrode 230, the number of lithium replenishing particles is multiple; the sum of the areas defined by the inner contours of the multiple coating layers is S3, and the sum of the areas defined by the outer contours of the multiple substrates after the lithium replenishing particles release lithium ions is S4. Then, the shrinkage area S of the multiple lithium replenishing particles during the lithium replenishment process satisfies the relationship: S = S3 - S4, and S has a range of 80μm. 2 ≤S / w1≤500μm 2 .
[0111] Specifically, the value of S / w1 can be, but is not limited to, 80 μm. 2 85μm 2 100μm 2 125μm 2 140μm 2 160μm 2 180μm 2 200μm 2 220μm 2 245μm 2 260μm 2 275μm 2 300μm 2 325μm 2 350μm 2 360μm 2 380μm 2 400μm 2 425μm 2 450μm 2 470μm 2 485μm 2 490μm 2 and 500μm 2 wait.
[0112] Understandably, a rectangular region of 22μm × 15μm is a rectangular region with a length of 22μm and a width of 15μm.
[0113] In this embodiment, within a specific magnification and a specific region, the sum of the areas defined by the inner contours of the multiple coating layers, S3, represents the sum of the areas of the matrix of the multiple lithium replenishment particles before shrinkage, and the sum of the areas defined by the outer contours of the multiple matrixes, S4, represents the sum of the areas of the matrix of the multiple lithium replenishment particles after shrinkage. The difference between S3 and S4 is the shrinkage area S of the multiple lithium replenishment particles during the lithium replenishment process. The shrinkage area S of the multiple lithium replenishment particles during the lithium replenishment process can characterize the amount of lithium released by the multiple lithium replenishment particles during the lithium replenishment process. When the value of S / w1 meets the range of 80 μm...2 ≤S / w1≤500μm 2 At the same time, the ratio of the shrinkage area of the multiple lithium replenishing particles during the lithium replenishment process to the mass fraction w1 of the first additive is within a reasonable range. On the one hand, the amount of lithium ions released by the multiple lithium replenishing particles during the lithium replenishment process is within a reasonable range, so that the lithium ions released by the multiple lithium replenishing particles can replenish the active ions lost by the battery 200 during charging and discharging in a timely manner, so that the battery 200 has a high energy density. On the other hand, the mass ratio of the first additive in the electrolyte 100 is within a reasonable range. In the first additive, multiple chain compounds with isocyanate end groups intersect in pairs and form a film attached to the surface of the lithium replenishing particles, and the thickness of the film formed by the first additive is within a reasonable range, so that the first additive can effectively prevent the electrolyte 100 from undergoing side reactions with oxygen, and can avoid the film formed by the first additive from being too thick and increasing the impedance, so that the electrolyte 100 has good stability performance, and ultimately the battery 200 has both high cycle performance and energy efficiency. When the S / w1 value is too high, the shrinkage area of the multiple lithium replenishing particles during the lithium replenishment process in the battery 200 is too large, or the mass fraction of the first additive is too small. When the battery 200 is charged, the total amount of lithium ions released by the multiple lithium replenishing particles is excessive. Although this can replenish the active ions lost during the charging and discharging process of the battery 200, it also generates excessive oxygen. Conversely, if the mass fraction of the first additive is too small, the first additive is difficult to polymerize into a film, or the polymerized film is too thin, making it difficult for the first additive to adhere to the surface of the lithium replenishing particles. This causes the oxygen generated by the lithium replenishing particles to still leak out and react with the electrolyte 100, resulting in poor stability of the electrolyte 100, and consequently, poor cycle performance and safety performance of the battery 200. When the S / w1 value is too low, the shrinkage area of the multiple lithium replenishing particles during the lithium replenishment process in the battery 200 is too small, or the mass fraction of the first additive is too large. When the battery 200 is charged, the total amount of lithium ions released by the lithium replenishing particles is too small, making it difficult for the particles to replenish the active ions lost during the charging and discharging process. Furthermore, the first additive has an excessively high mass proportion in the electrolyte 100, resulting in a thicker film formed by its polymerization reaction. This increases the resistance to the extraction of active ions from the surface of the positive electrode 230, thus affecting the energy density and energy efficiency of the battery 200.
[0114] In some embodiments, the shrinkage area S of the plurality of lithium replenishment particles during the lithium replenishment process ranges from 0.1 μm. 2 ≤S≤6μm 2 .
[0115] Specifically, the value of S can be, but is not limited to, 0.1 μm. 2 0.5μm 2 0.8μm 2 1μm 2 1.2μm 2 1.5μm 2 2μm 2 2.2μm 2 2.5μm 2 3μm 2 3.2μm 2 3.5μm 2 3.8μm 2 4μm 2 4.5μm 2 4.8μm 2 5μm 2 5.2μm 2 5.6μm 2 5.8μm 2 and 6μm 2 wait.
[0116] In this embodiment, when the shrinkage area S of the plurality of lithium replenishment particles during the lithium replenishment process meets the range of 0.1 μm 2 ≤S≤6μm 2 During the lithium replenishment process, the amount of lithium ions released by the multiple lithium replenishment particles is within a reasonable range. During the charging of the battery 200, the amount of lithium released by the multiple lithium replenishment particles is within a reasonable range, ensuring that the lithium replenishment particles can replenish the lithium ions lost during charging and discharging of the battery 200, while avoiding the release of excessive oxygen that could exacerbate side reactions with the electrolyte 100. Ultimately, this results in the battery 200 possessing both high energy density and good cycle performance and safety. However, when the shrinkage area S of the multiple lithium replenishment particles during the lithium replenishment process is too large, the amount of lithium released by the particles is excessive. Similarly, the oxygen released by the particles is also excessive, which may exacerbate the side reactions between the electrolyte 100 and oxygen, reducing the stability of the electrolyte 100 and the cycle performance of the battery 200. When the shrinkage area S of the multiple lithium replenishment particles during the lithium replenishment process is too small, the amount of lithium released by the multiple lithium replenishment particles during the lithium replenishment process is too small, and the amount of lithium ions released by the multiple lithium replenishment particles is too small, making it difficult for the lithium replenishment particles to replenish the lithium ions lost by the battery 200 during the charging and discharging process, thereby reducing the energy density of the battery 200.
[0117] Optionally, in some embodiments, the battery 200 satisfies the relationship: 0.5≤(w1+w2) / w3≤1.5.
[0118] Specifically, the value of (w1+w2) / w3 can be, but is not limited to, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 1.0, 1.1, 1.15, 1.2, 1.25, 1.3, 1.4, 1.45, and 1.5.
[0119] In this embodiment, when the battery 200 satisfies the relationship 0.5 ≤ (w1 + w2) / w3 ≤ 1.5, the mass fractions w1 of the first additive, w2 of the second additive, and w3 of the lithium replenishing particles are all within a reasonable range. In the battery 200, the chain compounds with isocyanate end groups in the first additive interlock to form a film on the surface of the lithium replenishing particles, thereby mitigating the side reactions between the lithium replenishing particles and the electrolyte 100. Furthermore, the boron atoms in the second additive can combine with the oxygen anions released by the lithium replenishing particles to generate oxygen, further mitigating the side reactions between the electrolyte 100 and oxygen. The first and second additives work synergistically to improve the stability of the electrolyte 100 while the lithium replenishing particles replenish lithium in the battery 200, further reducing the side reactions between the lithium replenishing particles and the electrolyte 100. When the value of (w1+w2) / w3 is too large, the mass fractions of the first and second additives are too high, or the mass fraction of the lithium replenishing particles is too low. This makes it difficult for the lithium replenishing particles to replenish the lithium ions lost during the charging and discharging process of the battery 200. In addition, excessive amounts of the first and second additives result in an excessively thick interfacial film between the positive electrode 230 and the electrolyte 100, increasing the interfacial resistance of active ions between the positive electrode 230 and the electrolyte 100, thereby affecting the kinetic performance of the interface between the positive electrode 230 and the electrolyte 100. When the value of (w1+w2) / w3 is too small, the mass fractions of the first and second additives are too small, or the mass fraction of the lithium replenishing particles is too high. This causes the lithium replenishing particles to release excessive oxygen during the charging and discharging of the battery 200. The first additive is unable to prevent the side reactions between the lithium replenishing particles and the electrolyte 100, and the second additive is unable to combine with the oxygen anions released by the lithium replenishing particles to generate oxygen, resulting in poor stability of the electrolyte 100.
[0120] The technical solution of this application will be further described below with reference to several embodiments.
[0121] Examples 1 to 18, Comparative Examples 1 to 8:
[0122] 1. Preparation of positive electrode 230:
[0123] A positive electrode active material (e.g., lithium iron phosphate), lithium replenishing particles (e.g., with Li5FeO4 as the matrix and a coating layer of Al2O3@C, or with Li6CoO4 as the matrix and a carbon coating layer), a positive electrode conductive agent (e.g., conductive carbon black), and a positive electrode binder (e.g., polyvinylidene fluoride) are dispersed in the solvent N-methylpyrrolidone and mixed evenly to obtain a positive electrode slurry. In the positive electrode slurry, the mass fraction of the positive electrode active material: the mass fraction of the positive electrode conductive agent: the mass fraction of the positive electrode binder is 96%:0.5%:2.3%. The positive electrode slurry is coated onto the positive electrode current collector layer 232 (e.g., aluminum foil). The unit area of the positive electrode slurry is 1540.25 mm². 2 The coating weight was 254 mg to form the positive electrode active layer 231. After drying, cold pressing, slitting, and cutting, positive electrode sheets 230 of Examples 1 to 18 and Comparative Examples 1 to 8 were obtained. The lithium replenishment particles of Examples 1 to 17 and Comparative Examples 1 to 8 used Li5FeO4 as the substrate and the chemical formula of the coating layer was Al2O3@C. The lithium replenishment particles of Example 18 used Li6CoO4 as the substrate and the coating layer was a carbon coating layer. The mass fraction w3 of the lithium replenishment particles of Examples 1 to 18 and Comparative Examples 1 to 8, the planar shrinkage rate α of the substrate, and the shrinkage area S of multiple lithium replenishment particles during the lithium replenishment process are shown in Table 1.
[0124] 2. Preparation of negative electrode 210 and separator 220:
[0125] A negative electrode active material (e.g., artificial graphite), a negative electrode conductive agent (e.g., conductive carbon black), a negative electrode thickener (e.g., carboxymethyl cellulose), and a negative electrode binder (e.g., styrene-butadiene rubber) are dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry is coated on a negative electrode current collector layer (e.g., copper foil). The coating weight of the negative electrode slurry per unit area (1540.25 mm2) is 122 mg. After drying, cold pressing, slitting, and cutting, negative electrode sheets 210 of Examples 1 to 18 and Comparative Examples 1 to 8 are obtained.
[0126] A polyethylene diaphragm 220 with a thickness of 16μm was selected.
[0127] 3. Preparation of electrolyte 100:
[0128] In an argon-atmosphere glove box with a moisture content ≤1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate were mixed in a mass ratio of 1:1:1. Then, dried lithium hexafluorophosphate electrolyte was dissolved in the solvent and stirred until completely dissolved and homogeneous. First additive, second additive, and third additive were added and mixed thoroughly to obtain electrolyte 100. The lithium salt concentration was 1 mol / L, and the mass fraction of the third additive in electrolyte 100 was 3%. The types and mass fractions (w1) of the first additive and the second additive (w2) in electrolyte 100 of Examples 1 to 18 and Comparative Examples 1 to 8 are shown in Table 1.
[0129] 4. Assembly of battery 200:
[0130] The positive electrode 230, separator 220, and negative electrode 210 of Examples 1 to 18 and Comparative Examples 1 to 8 prepared above are stacked in sequence, with the separator 220 positioned between the positive electrode 230 and the negative electrode 210. Then, they are wound to obtain a bare cell. The bare cell is placed in an outer packaging, dried, and then injected with the electrolyte 100. After standing, formation, and packaging processes, implementation cells 1 to 18 and control cells 1 to 8 are obtained. The positive electrode 230 and electrolyte 100 of Example 1 are disposed in implementation cell 1, the positive electrode 230 and electrolyte 100 of Example 2 are disposed in implementation cell 2, the positive electrode 230 and electrolyte 100 of control cell 1 are disposed in control cell 1, and so on.
[0131] The method for testing the planar shrinkage rate α of the substrate in the positive electrode 230 is as follows:
[0132] Please see Figure 3 and Figure 4 The positive electrode 230 is assembled into the battery 200 and the battery 200 is charged. The positive electrode 230 is then disassembled and cut using an ion beam polishing (CP) instrument to obtain a cross-section of the positive electrode 230. The positive electrode 230 is observed using a scanning electron microscope (SEM) and photographed at a magnification of 10K. Figure 3 This is a scanning electron microscope image of lithium-replenishing particles after shrinkage, according to an embodiment of this application. Figure 3The diagram illustrates the sampling of points along the inner contour of the coating layer. Using image analysis software and employing polygon measurement, points are sampled along the inner contour of the coating layer, and the area S1 defined by the inner contour of the coating layer is calculated using the image analysis software. The area defined by the inner contour of the coating layer is the area of the substrate before shrinkage. Figure 4 This is a scanning electron microscope image of the lithium-replenishing particles after shrinkage, according to another embodiment of this application. Figure 4 The diagram illustrates the sampling of points along the outer contour of the substrate. Using image analysis software, the area S2 defined by the outer contour of the substrate is calculated. This area is the area of the substrate after shrinkage. The planar shrinkage rate α of the substrate then satisfies the following formula: α = (S1 - S2) / S1 × 100%. The planar shrinkage rate α of the substrate is controlled by adjusting the voltage of the battery 200 to its maximum value.
[0133] The method for testing the shrinkage area S of the multiple substrates in the positive electrode 230 during the lithium replenishment process is as follows:
[0134] The positive electrode 230 is assembled into the battery 200 and the battery 200 is charged. The positive electrode 230 is then disassembled and cut using an ion beam polishing (CP) instrument to obtain a cross-section of the positive electrode 230. The positive electrode 230 is observed using a scanning electron microscope (SEM) at a magnification of 5K. Within a rectangular area of 22μm × 15μm, the sum of the areas defined by the inner contours of the multiple coating layers is S3, which is the total area of the multiple lithium replenishment particles before shrinkage; the sum of the areas defined by the outer contours of the multiple substrates is S4, which is the total area of the multiple lithium replenishment particles after shrinkage; therefore, the shrinkage area of the multiple substrates during the lithium replenishment process is S = S3 - S4.
[0135] Table 1 below shows the structural parameters of the electrolyte 100 and battery 200 of Examples 1 to 18 and Comparative Examples 1 to 8.
[0136]
[0137]
[0138] Table 1: Structural parameters of electrolyte 100 and battery 200 in Examples 1 to 18, and Comparative Examples 1 to 8.
[0139] Battery 200 performance test:
[0140] Batteries 1 to 18 (Example) and 1 to 8 (Comparative) were left to stand at 25°C for 1 hour, then charged at 0.5P to 3.65V, and then discharged at 0.5P to 2.5V. The initial discharge capacity C1 and initial discharge energy E1 of battery 200 were recorded. Batteries 1 to 18 (Example) and 1 to 8 (Comparative) were cycled through one charge-discharge cycle, and the discharge capacity C1 was recorded. Batteries 1 to 18 (Example) and 1 to 8 (Comparative) were cycled through 500 charge-discharge cycles, and the discharge capacity C1 was recorded. 500 Discharge energy E 500 and charging energy E' 500 The energy efficiency E = E1 of the implementation batteries 1 to 18 and the comparative batteries 1 to 8 was obtained. 500 / E' 500 ×100%, the capacity retention rate Cf = Cimplementation after 500 cycles of implementation batteries 1 to 18 and control batteries 1 to 8 is obtained. 500 / C1×100%. The energy efficiency E and capacity retention Cf of the implementation batteries 1 to 18 and the control batteries 1 to 8 after 500 cycles are shown in Table 2.
[0141] Table 2 below shows the performance parameters of implementation batteries 1 to 18 and comparative batteries 1 to 8.
[0142]
[0143]
[0144] Table 2: Performance parameters of implementation batteries 1 to 18 and comparative batteries 1 to 8.
[0145] Please refer to Tables 1 and 2. From the data of Examples 1 to 3, Comparative Examples 1 and 2, it can be seen that the planar shrinkage rate α of the substrate in Examples 1 to 3 all meet the range of 5% ≤ α ≤ 40%. In Comparative Example 1, the planar shrinkage rate α of the substrate is less than 5%, and in Comparative Example 2, the planar shrinkage rate α of the substrate is greater than 40%. This makes the capacity retention rate of Implemented Battery 1 to Implemented Battery 3 after 500 cycles greater than that of Comparative Battery 1 and Comparative Battery 2 after 500 cycles, and the energy efficiency of Implemented Battery 1 to Implemented Battery 3 after 500 cycles is greater than that of Comparative Battery 2 after 500 cycles. This is because when the planar shrinkage rate α of the substrate is within a reasonable range, the shrinkage area S of multiple lithium replenishment particles during the lithium replenishment process is also within a reasonable range. During the charging process of the battery 200, the amount of lithium released by the lithium replenishment particles during the lithium replenishment process is within a reasonable range. This allows the lithium replenishment particles to replenish the lithium ions lost by the battery 200 during charging and discharging, while also preventing the lithium replenishment particles from releasing too much oxygen, which would exacerbate the side reactions with the electrolyte 100. Ultimately, this allows the battery 200 to have both high energy density and good cycle performance and safety performance.
[0146] As shown by the data from Examples 2, 4, and 5, the mass fraction of the lithium replenishing particles in Examples 4, 2, and 5 gradually increases, leading to a gradual increase in the value of α×w3 / w1 and a gradual decrease in the value of (w1+w2) / w3. This results in the capacity retention rate of Battery 4, Battery 2, and Battery 5 after 500 cycles initially increasing and then decreasing, while the energy efficiency of Battery 4, Battery 2, and Battery 5 after 500 cycles decreases sequentially. This is because as the mass fraction w3 of the lithium replenishing particles gradually increases, α×w3 / w1 gradually increases, resulting in more lithium ions released by the particles, improving the lithium replenishment effect and cycle stability. Consequently, Battery 4 exhibits higher cycle stability compared to Battery 2. However, correspondingly, the lithium replenishment particles release oxygen along with lithium ions. The increased amount of oxygen may lead to an increase in side reactions between oxygen and electrolyte 100, reducing the cycle stability of battery 5. To alleviate the increased gas production, more first additive is needed to reduce the side reactions between lithium replenishment particles and electrolyte 100. However, the film formed by the polymerization of the first additive will increase the resistance of active ions to escape from the surface of the positive electrode, thereby affecting the energy density of the battery and causing the energy efficiency of batteries 4, 2, and 5 to gradually decrease.
[0147] As can be seen from the data of Examples 6 to 8 and Comparative Example 3, the value of n in the chemical formula of the first additive in Examples 6 to 8 satisfies the range 1≤n≤15, while the value of n in the chemical formula of the first additive in Comparative Example 3 is greater than 15. This makes the capacity retention rate of the comparative battery 3 after 500 cycles lower than that of the experimental batteries 6 to 8 after 500 cycles, and the energy efficiency of the comparative battery 3 after 500 cycles is lower than that of the experimental batteries 6 to 8 after 500 cycles. This is because: when the value of n is too large, when the mass fraction of the first additive is constant, the carbon chain of the chain compound is too long, resulting in a smaller mass proportion of isocyanate. This is not conducive to the polymerization reaction of two adjacent chain compounds to form a film and adhere to the surface of the lithium supplement particles, making it difficult to prevent the side reaction between the electrolyte 100 and oxygen, reducing the stability of the electrolyte 100, and thus reducing the capacity retention rate of the battery 200. Furthermore, when the first additive undergoes a polymerization reaction and forms a film, the interfacial impedance between the electrolyte 100 and the film becomes too large, thereby reducing the energy efficiency of the electrolyte 100 when applied to the battery 200.
[0148] From the data of Examples 9 and 10, and Comparative Examples 4, 5, and 8, it can be seen that the mass fraction w1 of the first additive in Examples 9 and 10 satisfies the range 0.01% ≤ w1 ≤ 3%, while Comparative Examples 4 and 8 do not include the first additive, and the mass fraction of the first additive in Comparative Example 5 is greater than 3%. This results in the battery 9 and battery 10 having a higher capacity retention rate after 500 cycles than the battery 4, battery 5, and battery 8, and the battery 9 and battery 10 having a higher energy efficiency after 500 cycles than the battery 4, battery 5, and battery 8. The high energy efficiency after 500 cycles is due to the following: In both battery 9 and battery 10, the mass fraction of the first additive is within a reasonable range. In the first additive, multiple chain compounds with isocyanate end groups intersect in pairs to form a film attached to the surface of the lithium-replenishing particles. Furthermore, the thickness of the film formed by the first additive is within a reasonable range, effectively preventing side reactions between the electrolyte 100 and oxygen, and avoiding excessively thick films that increase impedance. This results in good stability of the electrolyte 100, and the battery 200 exhibits both high cycle performance and energy efficiency. In contrast, comparative batteries 4 and 8 do not include the first additive, increasing the probability of side reactions between the lithium-replenishing particles and the electrolyte 100. The generated reactants also increase interfacial impedance, leading to poorer cycle performance and lower energy efficiency in comparative batteries 4 and 8. In the comparative battery 5, the mass fraction of the first additive is too large, and the film formed by the first additive is thicker. This increases the resistance of active ions to being extracted from the surface of the positive electrode 230, thereby affecting the kinetic performance of the interface between the positive electrode 230 and the electrolyte 100 and reducing the energy efficiency of the comparative battery 5.
[0149] As can be seen from the data of Examples 11 to 13, the second additive in Example 11 is lithium bis(oxalato)borate, the second additive in Example 12 is lithium tetrafluoroborate, and the second additive in Example 13 is lithium bis(trifluoromethyl)difluoroborate. As can be seen from the performance parameters of the batteries 11 to 13, the boron atoms in lithium bis(oxalato)borate, lithium tetrafluoroborate, and lithium bis(trifluoromethyl)difluoroborate can combine with oxygen negative ions to reduce the amount of oxygen generated by the reaction of oxygen negative ions with iron ions, further slowing down the side reaction between electrolyte 100 and oxygen, so that electrolyte 100 has higher stability, thereby enabling battery 200 to have a higher capacity retention rate and energy efficiency after 500 cycles.
[0150] As can be seen from the data of Examples 14 and 15, and Comparative Examples 6 to 8, the mass fraction w2 of the second additive in Examples 14 and 15 satisfies the range 0.01% ≤ w2 ≤ 3%, while Comparative Examples 6 and 8 do not include the second additive, and the mass fraction of the second additive in Comparative Example 7 is greater than 3%. This results in the higher capacity retention rate of Implemented Battery 14 and Implemented Battery 15 after 500 cycles compared to Comparative Batteries 6 to 8, and the higher energy efficiency of Implemented Battery 14 and Implemented Battery 15 after 500 cycles compared to Comparative Batteries 6 to 8. This is because the mass fraction of the second additive in Implemented Battery 14 and Implemented Battery 15 is within a reasonable range. Furthermore, the boron atom content in the second additive is within a reasonable range, allowing it to combine with the oxygen anions released by the lithium-filled particles to generate oxygen, thereby mitigating the side reaction between the electrolyte 100 and oxygen, thus improving the stability of the electrolyte 100 and enhancing the capacity retention rate of Implemented Battery 14 and Implemented Battery 15. Furthermore, it avoids reduction reactions caused by an excessively high mass fraction of the second additive, which would increase the interfacial resistance between the positive electrode 230 and the electrolyte 100. This allows both experimental batteries 14 and 15 to maintain high energy efficiency. In contrast, comparative batteries 6 and 8, lacking the second additive, increase the probability of oxygen ions released from lithium-ion particles combining with iron ions to generate oxygen, reducing the stability of the electrolyte 100 and resulting in lower capacity retention. In comparative battery 7, the excessive mass fraction of the second additive could cause excess additive to adhere to the interface between the positive electrode 230 and the electrolyte 100, undergoing a reduction reaction and generating decomposition products that adhere to the surface of the positive electrode 230. This increases the resistance to the insertion and extraction of active ions on the positive electrode 230, leading to lower energy efficiency in comparative battery 7.
[0151] As can be seen from the data of Examples 16 and 17, the values of (w1+w2) / w3 in Examples 16 and 17 both satisfy the range 0.5≤(w1+w2) / w3≤1.5, and the value of (w1+w2) / w3 in Example 16 is greater than the value of (w1+w2) / w3 in Example 17. This makes the capacity retention rate of battery 16 after 500 cycles greater than that of battery 17 after 500 cycles, and the energy efficiency of battery 17 after 500 cycles greater than that of battery 16 after 500 cycles. This is because the value of (w1+w2) / w3 in battery 16 is greater than that in battery 17. If the value of (w1+w2) / w3 is too high, then in battery 16, the mass fraction of the first additive and the mass fraction of the second additive are too high, or the mass fraction of the lithium replenishing particles is too low, making it difficult for the lithium replenishing particles to replenish the lithium ions lost by battery 200 during charging and discharging. In addition, excessive amounts of the first additive and the second additive make the interface film between the positive electrode 230 and the electrolyte 100 too thick, increasing the interfacial resistance of active ions between the positive electrode 230 and the electrolyte 100, thereby affecting the kinetic performance of the interface between the positive electrode 230 and the electrolyte 100, resulting in the energy efficiency of battery 16 being lower than that of battery 17. In battery 17, the value of (w1+w2) / w3 is smaller, resulting in smaller mass fractions of the first and second additives, or a larger mass fraction of the lithium replenishing particles. This causes the lithium replenishing particles to release excessive oxygen during charging and discharging of battery 200, increasing the difficulty for the first additive to prevent side reactions between the lithium replenishing particles and electrolyte 100. Consequently, the stability of electrolyte 100 in battery 17 is poor, leading to a lower capacity retention rate for battery 17 compared to battery 16.
[0152] Data from Examples 18 and 2 show that, under identical conditions, the lithium replenishment particles of Example 2 use Li5FeO4 as the substrate and the coating layer has the chemical formula Al2O3@C, while the lithium replenishment particles of Example 18 use Li6CoO4 as the substrate and the coating layer is a carbon coating layer. This results in the battery 2 having a higher capacity retention rate after 500 cycles than the battery 18, and the energy efficiency of the battery 2 after 500 cycles is not significantly different from that of the battery 18. This indicates that the method of using Li6CoO4 as the substrate and a carbon coating layer for the lithium replenishment particles is superior to using Li6CoO4 as the substrate and a carbon coating layer for the lithium replenishment particles.
[0153] Please see Figure 5 and Figure 6This application also provides an electrical device 300, which includes a device body 310 and a battery 200 provided in this application, wherein the battery 200 supplies power to the device body 310.
[0154] Understandably, the battery 200 is electrically connected to the device body 310.
[0155] In this embodiment, the battery 200 has good cycle performance and safety performance, as well as high energy efficiency, resulting in a long service life. When the battery 200 is used to power the device body 310, it can provide a stable power supply to the device body 310, enabling the device body 310 to operate normally.
[0156] Optionally, the electrical device 300 in this application embodiment can be, but is not limited to, portable electronic devices such as mobile phones, tablets, laptops, desktop computers, smart bracelets, smartwatches, e-readers, and game consoles. It can also be a vehicle such as a car, truck, sedan, van, freight train, high-speed train, or electric vehicle. Furthermore, it can be various household appliances. Figure 6 The electrical equipment 300 in this embodiment is an energy storage battery cabinet.
[0157] It is understood that the electrical device 300 described in this embodiment is merely one form of the electrical device 300 used by the battery 200, and should not be construed as a limitation on the electrical device 300 provided in this application, nor should it be construed as a limitation on the electrical device 300 provided in various embodiments of this application.
[0158] In this application, the terms "embodiment" and "implementation" mean that a specific feature, structure, or characteristic described in connection with an embodiment can be included in at least one embodiment of this application. The appearance of these phrases in various locations throughout the specification does not necessarily refer to the same embodiment, nor are they independent or alternative embodiments mutually exclusive with other embodiments. Those skilled in the art will understand, explicitly and implicitly, that the embodiments described in this application can be combined with other embodiments. Furthermore, it should be understood that the features, structures, or characteristics described in the various embodiments of this application can be arbitrarily combined to form another embodiment that does not depart from the spirit and scope of the technical solution of this application, provided there is no contradiction between them.
[0159] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit it. Although this application has been described in detail with reference to the above preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions to the technical solutions of this application should not depart from the spirit and scope of the technical solutions of this application.
Claims
1. A battery, characterized in that, The battery includes: Negative electrode sheet; A diaphragm is disposed on one side of the negative electrode sheet; A positive electrode sheet is disposed on the side of the separator opposite to the negative electrode sheet. The positive electrode sheet includes a positive active layer and a positive current collector layer. The positive active layer is disposed on the surface of the positive current collector layer and includes a plurality of lithium-filling particles. An electrolyte, which infiltrates at least part of the positive electrode plate and at least part of the negative electrode plate, and the electrolyte further comprises a lithium salt; the electrolyte comprises a first additive, and the first additive comprises a linear compound with isocyanate groups as end groups, wherein the mass fraction w1 of the first additive in the electrolyte satisfies the range: 0.01% ≤ w1 ≤ 3%; in the positive active layer, the mass fraction of the lithium-supplementing particles is w3; the lithium-supplementing particles comprise a matrix and a coating layer, the coating layer is disposed on the outer periphery of the matrix, and the plane shrinkage rate of the matrix is α; then the relational expression 0.2 ≤ α×w3 / w1 ≤ 1 is satisfied; wherein the chemical formula of the matrix is Li 1+r M 1-p N p O 4-s B s , which satisfies 0.1 < r < 6.1, 0 ≤ p < 0.99, 0 ≤ s < 0.1; M and N are each selected from at least one of iron, cobalt, nickel, titanium, zinc, magnesium, aluminum, manganese, vanadium, chromium, zirconium, copper, niobium, tantalum, tungsten, yttrium and lanthanum, and B is selected from at least one of sulfur, nitrogen, fluorine, chlorine and bromine; in the cross-section of the positive electrode plate, the area defined by the inner contour of the coating layer is S1, and after the lithium-supplementing particles release lithium ions, the area defined by the outer contour of the matrix is S2, then the plane shrinkage rate α of the matrix satisfies the relational expression: α=(S1-S2) / S1×100%, and the range of the plane shrinkage rate α of the matrix is 5% ≤ α ≤ 40%.
2. The battery according to claim 1, characterized in that, The chemical formula of the first additive is: OCN-(CH2) n -NCO, where n has a range of 1 ≤ n ≤ 15.
3. The battery according to claim 1, characterized in that, The electrolyte also includes a second additive and a solvent, wherein the oxidation potential of the second additive is lower than that of the solvent, and the second additive is a borate additive.
4. The battery according to claim 3, characterized in that, In the electrolyte, the mass fraction w2 of the second additive is in the range of 0.01% ≤ w2 ≤ 3%.
5. The battery according to claim 3, characterized in that, The second additive includes at least one of lithium difluorooxalate borate, lithium bis(oxalate borate), lithium tetrafluoroborate, lithium tetraborate, lithium tetracyanoborate, lithium difluoroborate, lithium tetra(trifluoromethyl)borate, lithium bis(trifluoromethyl)difluoroborate, lithium dicyanooxalate borate, lithium pentafluoroethyl trifluoroborate, and lithium perfluorotert-butoxy trifluoroborate.
6. The battery according to claim 1, characterized in that, In the positive electrode active layer, the mass fraction w3 of the lithium replenishment particles is in the range of 0.5% ≤ w3 ≤ 5%.
7. The battery according to claim 1, characterized in that, At a magnification of 5000x, within a rectangular region of 22μm × 15μm, in the cross-section of the positive electrode sheet, there are multiple lithium replenishment particles. The sum of the areas defined by the inner contours of the multiple coating layers is S3, and the sum of the areas defined by the outer contours of the multiple substrates after the lithium replenishment particles release lithium ions is S4. Therefore, the shrinkage area S of the multiple lithium replenishment particles during the lithium replenishment process satisfies the relationship: S = S3 - S4, and S has a range of 80μm. 2 ≤S / w1≤500μm 2 .
8. The battery according to claim 7, characterized in that, The shrinkage area S of the plurality of lithium replenishment particles during the lithium replenishment process ranges from 0.1 μm. 2 ≤S≤6μm 2 .
9. An electrical appliance, characterized in that, The electrical equipment includes: The equipment itself; and The battery according to any one of claims 1 to 8, wherein the battery supplies power to the device body.
Citation Information
Patent Citations
Lithium ion battery and anode lithium supplementing method thereof
CN114583296A
Positive lithium supplement additive, preparation method thereof, positive plate and secondary battery
CN115513457A
Lithium ion battery electrolyte and lithium ion battery thereof
CN115995607A